“That load of Jews is finally dead.” Extermination of Jews as presented in 1942 letters of German soldiers - Marcin Zaremba (Zagłada Żydów)
The Home Army intelligence intercepted letters written by German officers and clerks to their families as well as those sent from Germany to friends and relatives on the front line. On the basis of that correspondence the Polish underground drafted special intelligence reports, which were sent to London. The selection of letters devoted to the Holocaust presented in this article can make it easier to describe and understand the stances and opinions of “ordinary Germans” regarding the “final solution.”